STUDI PARAMETRIK GAS RECYCLING PADA RESERVOIR MINYAK DENGAN METODE MATERIAL BALANCE ANALYSIS - Nur Agista, Madhan
Along with the difficulty to get the energy source from hydrocarbons, production management of a reservoir is very important in order to get a recovery factor as much as possible. Gas recycling is one of the reservoir production management methods which commonly used in the petroleum industry in order raising the recovery of oil/condensate and aims to maintain reservoir pressure not to decline. Gas recycling is the process of reinjection produced gas into the reservoir. Material balance method is used in this study to see the effect of the quantity of gas that injected to the gas and oil recovery in the gas recycling process by take an advantage in simplicity of the model and less time in running model. The study conduct in the X field which located in the Natuna Sea. X filed has three productive zones : two oil zones and a gas zone. Gas recycling is applied at the main oil zone ( Asso_1 ). The study begins by making a tank model which continued by history matching, and then resumed in production systems. Base case in this study is to inject the entire gas that produced (100%) into the reservoir. Another scenario is a quantity reduction of gas injection to 80%, 60%, 40%, 20% and 0%. Prediction start in February 2014 and end in January 2028. Results showed that 100 % scenario has a maximum in oil recovery but no gas that can be sold or utilized. While 0% scenario has a minimum in oil recovery but maximum in net gas that can be utilized or sold. Obtained from both plots the 38% scenario is a scenario in which the cumulative net gas and cumulative oil have the same value.